Industrial training report: Perbadanan Perpustakaan Awam Selangor (Selangor) / Muhammad Syafiq Zul Hadim - Zul Hadim, Muhammad Syafiq (Perpustakaan Tengku Anis, 2019)
The trainee internship at Perbadanan Perpustakaan Awam Selangor Malaysia in department Information Technology started from 2nd February 2019 until 28th June 2019. During the internship program the trainee are involve in corporate video of the Perbadanan Perpustakaan Awam Selangor production in order to highlight services and facility that they provided to the public user based on method of pre-production, production, and postproduction which relate to technical task.. Besides, the trainee have involve in several activity which maintenances, marketing, technical task and live session production and sharing in Perbadanan Perpustakaan Awam Selangor production. Next, the trainee also involved on conducting events, program and class which be held in the Perbadanan Perpustakaan Awam Selangor .The trainee can learn something news during internship program and also can implements the knowledge that learns at faculty towards internship program.